Autonomia decisória do idoso com câncer: percepções do idoso, da família e da equipe de saúde - Kreuz, Giovana (2017)
Considering the population aging and its association with the estimation of grow cases of cancer in Brazil for the 2016 and 2017 years, being the elderly as the most susceptible to that disease, emerge the need to rethink the perceptions about old age and autonomy. This work proposes to analyze the perception of participation of elderly patients with cancer in decisions on their treatments, from patients, relatives, and health care team points of view, and more specifically analyzes intervenient aspects in the participation of elderly person with cancer in decisions about their own treatments. Data were collected through semi-structured interviews with 5 older patients under cancer treatment, 3 family members and 4 health professionals during the hospital stay. Content analysis and interpretation was developed based on the theoretical foundations for qualitative research of Bardin (2011) and Strauss and Corbin (2008), allowing the elaboration of the categories: autonomy, which addresses shared autonomy and the delegation of autonomy; loss of autonomy, approaching dependence; health and disease in old age, approaching the perceptions between disease and aging and the terminologies used to designate the elderly and the old age; autonomy and finitude, approaching the Advance Healthcare Directives and the relationship between the elderly and the health team. In the autonomy category, considering the diversity and heterogeneity of old age, and accepting the interlocution of various knowledge, the results indicate that the elderly perceive autonomy as a possibility to manage aspects of their own life, indicating that their choices are recognized and respected. The relatives position themselves to respect the decisions of the elderly, allowing them to maintain autonomy, although age is pointed by health professionals as a family argument for the exclusion of the elderly from decision making. Health professionals affirm that autonomy should be maintained regardless of age, although they point cognition and absence of severe mental disorder as criteria for determine its maintenance. The report that the health team excludes the elderly from the decisionmaking process, when communicating with the family, established a counterpoint in an interview with a relative. Loss of autonomy category indicates the dependence as an obstacle to exercise autonomy, being feared by the majority of patients and perceived as different from needing or asking for help, revealing a changing status. Regarding health and illness in old age, the interviewed elderly did not associate cancer with age, but in family conception it was perceived as an important factor. In Portuguese, the word “velho” has negative and pejorative connotation, and “idoso” indicates respect and dignity towards the person. The autonomy and finitude category revealed that patients and their families are unaware of Advance Healthcare Directives, and the health team has a partial knowledge about it, so this alternative is not used in that health center. This study reveals nuances between the effectiveness of the elderly autonomy and the ideal perception presented by the participants of the research; autonomy can be configured in a self-centered, shared way or delegated, according to context and needs